Bioatividade de inseticidas botânicos sobre Microtheca ochroloma Stal (Coleoptera: Chrysomelidae) - Poncio, Sônia (2010)
The Chinese cabbage is a vegetable largely cultivated by organic farmers in the region of Santa Maria, RS. However, due to severe damage caused by the chrysomelid Microtheca ochroloma Stal, many of them are abandoning the crop. The use of botanical pesticides is an alternative for the control of these insect pests. Therefore, this study aimed to evaluate the action of commercial products and aqueous extracts of insecticide plants on the different stages of development, food consumption and biological aspects of M. ochroloma. In experiments conducted in laboratory, at a temperature of 25 ± 2ºC, relative humidity of 60 ± 10% and 14 hours of photophase, the effects of aqueous extracts of 10% w/v of Nicotiana tabacum L. (in the form of tobacco-powder), of leaves of Melia azedarach L., Eucalyptus citriodora Hook, Cedrella fissilis L., Trichilia claussenii C. DC., Blepharocalyx salicifolius (Kunth) O. Berg, Eugenia uniflora L., Cinnamomum camphora (L.) J. Presl, Syzygium cuminii L., Cymbopogon nardus (L.) Rendle, of leaves and twings of Ateleia glazioveana Baill, Senecio brasiliensis Less and Ruta graveolens L., of seeds of Azadirachta indica A. Juss, and the commercial products Organic Neem ®, 1 and 5% v / v, and Neem Azal T / S ®, 0.5 and 1% v / v, both elaborated from A. indica (neem) were assessed. The action of the treatments was tested on eggs up to 24 hours old; under direct contact and ingestion of three-day-old larvae, in which were assessed the viability of larvae and pupae, the larval period and the defective adults; and in adults with unknown age also under the action of contact and ingestion. In addition, leaf discs of Chinese cabbage were treated with different treatments and with distilled water (control) and offered to larvae and adults in free-choice and no-choice tests. The commercial products Neem Azal T / S and Organic Neem and the extracts of M. azedarach, of tobacco powder, of S. brasiliensis and of B. salicifolius, by causing mortality at different stages of development of M. ocrholoma and decrease in the consumption of treated leaves, and also the extract of E. uniflora due to its action in the biology of these insects, should be evaluated in field conditions as potential alternatives to be used for the control of M. ochroloma.